Use of an Auditory Brainstem Response (ABR) Simulator to Train Audiology Students on Labelling Peaks In The Auditory Brainstem Response - Dzulkarnain, Ahmad Aidil Arafat; Sapian, Faizah; Wilson, Wayne; Bradley, Andrew; Jamaluddin, Saiful Adli; Ali Hanafiah, Nurlin; Norddin, Narina (2012)
The auditory brainstem response (ABR) is a complex response that represents neural activity generated at several anatomical sites in response to particular types of external stimuli and consists of up to seven waves; each numbered using the Roman numeric system to give Waves I–VII. The ABR is also widely used in medical and health science field for example to determine the site of the lesion for retrocochlear pathologies and to estimate hearing sensitivity among children. One of the most problematic issues in ABR is the difficulty to correctly identify their respective peaks. Some of this difficulty stems from the large variation in ABR morphology in subjects with and without hearing loss, the variation in techniques for labeling peaks and the contribution from other physiological and non physiological activities. The task to identify ABR peaks therefore requires high clinical experience and knowledge since any misidentification of ABR peaks may lead to misinterpretation to the ABR results. Thus, this study has developed an ABR simulator for any educators who wish to teach their students to identify ABR peaks or for any clinicians who requires more training to improve their skills to identify ABR peaks. The ABR simulator consists of approximately 250 ABR waves from normal and subjects with hearing loss and the system will automatically tell the users if their identification is correct or wrong once the answer has been locked (Y-for correct answer and N-for wrong answer). In this paper we will share our initial findings where we have compared the performance of our student in determining ABR peaks using our simulator and conventional based training.